A Dose-Response Meta-Analysis of Dietary Fiber Intake and Breast Cancer Risk. (May 2022) - Xu, Kedi; Sun, Qiuyu; Shi, Ziang; Zou, Yuanlin; Jiang, Xiaoru; Wang, Yanli; Chong, Feifei; Song, Chunhua
Whether dietary fiber intake could reduce the risk of breast cancer (BC) is still controversial. The articles related to breast cancer and dietary fiber were retrieved through PubMed and Web of Science database. Summary relative risk (RR) and attributable risk percentage (ARP) for dietary fiber intake on the development of breast cancer were calculated. Dose-response meta-analysis modeled the relationship between dietary fiber intake and breast cancer risk. A total of 10 studies were included in this study. Meta-analysis showed that dietary fiber intake was negatively associated with breast cancer (RR = 0.83). In dose-response analysis, the risk of breast cancer showed a statistically significant linear trend with increasing dietary fiber dose: when adding 10 g per day, the risk decreased by 4.7% (RR = 0.95). The ARP results demonstrated that the breast cancer dietary fiber–attributed percentage was 33.33% in Asia, which was higher than 16.28% in North America and 9.89% in Europe. In conclusion, dietary fiber intake may have a positive effect on reducing breast cancer risk, especially in high doses.